ISLAM DAN FEMINISME (Perspektif Rekonstruksi Hukum Islam) - Ahmad Syukron (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2009)
We have almost all walks of life, echoes of the emancipation of women is sticking up all for human rights as a woman who has not had a chance they occupy the position, honor, glory and freedom is equal to a man of many dimensions of life. Islam as part of a religion, it is just very concerned with aspects of the “humanization of women”. Women are no longer just as an object of her husband and family services, but also it also depends on the human figure. Their responsibility before God is the same as men. They are also creatures who have the sacred nature of glory is not measured based on gender, but from their faith mission.